Association of polymorphism of some candidate genes with the development of non-infectious and infectious endocarditis - Yu. S. Bakhareva; V. N. Maksimov; E. I. Akinshina; N. N. Chapaeva (Российский кардиологический журнал, 2018)
Aim. To study association between polymorphisms of candidate genes and the development of non-infectious and infectious endocarditis (IE).Material and methods. During the study 175 patients were examined. They were divided into two groups: the first group — 81 patients with non-infectious endocarditis and the second one — 94 patients with IE. We present a comparative analysis of the genotype frequencies of the five genes polymorphisms: rs11697325 (-8202 A/G) of the MMP9 gene, 4a/4b of the NOS3 gene, rs4340 of the ACE gene, rs2476601 (С1858Т) of the PTPN22 gene, rs231775 (49 A/G) of the CTLA4 gene in groups of patients with endocarditis and healthy individuals.Results. We found association between endocarditis and rs11697325 (-8202 A/G) of the MMP9 gene, 4a/4b of the NOS3 gene, as well as rs2476601 (C1858T) of the PTPN22 gene with IE.Conclusion. Thus, association between three of the five polymorphisms and vegetations on the valvular heart apparatus was revealed.